Structural dynamic analysis of oil and gas transmission pipe - Wan, Dong Hua (2013)
This project was carried out as a study of structural dynamic analysis using ANSYS to simulate the system vibration. The objective of this project is to obtain dynamic characteristics of oil and gas transmission pipeline. In order to get the dynamic characteristics, the pipeline system should be designed to be used for the experiment and simulation test. Following the design system, setting the PVC material, then import the pipeline system into ANSYS to make modal analysis. Simulating the vibrate variation from 0 Hz to 600 Hz. According to the deformation of the pipeline system, to find where is the most serious deformation place. So the point what we find is the damping point, the frequency at this point is the natural frequency. Collecting all data of the natural frequency and mode shapes at the damping points. The second part is the experiment. Following the design system, assemble the entity system. Use the accelerometer sensor to convert pipeline system vibration to electrical as input data. Following the accelerometer, use the instrument driver to connect the accelerometer with the laptop. Lastly to start the experiment by the impact hammer knock the pipeline system, and then collect the data of natural frequencies, mode shapes and damping of the structural dynamic of the pipeline system. Comparing the mode shapes to select the natural frequency with the same mode shapes from the experiment and simulation.